Identification and Abundance of Macroalgae at Batu Layar Coast, West Lombok, Indonesia. Issue 1 (November 2021) - Kirana, I A P; Kurniawan, N S H; Abidin, A S; Nikmatullah, A; Sunarwidhi, A L; Jupri, A; Hernawan, A; Widyastuti, S; Sunarpi, H; Prasedya, E S
Abstract: Batu Layar coastal area provides an optimum environment for the diversity of coastal biota in the form of corals, crustaceans, molluscs, echinoderms and macroalgae. Macroalgae are plantlike marine biota that are large in size. Based on taxonomy, macroalgae are included in the Thallophyta group because their bodies are thallus. The purpose of this study is to evaluate the abundance of macroalgae in Batu Layar Coastal areas to be used as primary data for further research. This research is located at Batu Layar Coast using the Transect method. The number of transects used is 4 transects with the length of each transect is 50 m. On each transect, 5 stations were taken. Samples of each different macroalgae species at each station were taken for the purpose of morphological identification. Macroalgae identification is presented in the form of descriptive analysis and graphs in the presentation of diversity, evenness, and abundance. The results of the identification of macroalgae in research at Batu Layar Coast as a whole found that there were 24 species of macroalgae consisting of 11 species of Chlorophyta, 8 species of Rhodophyta and 5 species of Phaeophyta. Dominant species on the shoreline are Chlorophyta, in the middle of the transect most of algae are the Phaeophyta and dominant species farthest from the shore are Rhodophyta. The conclusion is the most abundant macroalgae species is Gelidium latifolium from Rhodophyta division with number of abundance is 4.58 individuals/m 2 .